'Special death': Living with bereavement by drug-related death in Ireland. Issue 10 (26th November 2022) - Lambert, Sharon; O'Callaghan, Daniel; Frost, Nollaig
Abstract: This paper explores the impact of complicated grief on the family system following the drug-related death of a family member. Drug-related deaths are rife with moral stigmas, and those left behind often carry an emotional burden laden with shame and guilt. 17 bereaved family members were interviewed using semi-structured interviews and transcripts were analyzed using reflexive thematic analysis. Three core themes were generated: Renegotiation of Relationships; Experiencing Complex Emotions; and Adjusting to a New Reality. The findings demonstrate that this population experience great difficulty in processing their grief as they struggle with family breakdown, navigating supports and stigma.